Detection of Trypanosoma cruzi in white-eared opossums (Didelphis albiventris) from Canoinhas, Santa Catarina State, Brazil - Pontarolo, Giane Helenita; Pedrassani, Daniela; Kühl, Luís Felipe; Campos, Monique Paiva; Tirado, Thais Cristina; Figueiredo, Fabiano Borges; Vieira, Thállitha Samih Wischral Jayme; Calchi, Ana Cláudia [UNESP]; André, Marcos Rogério [UNESP]; Vieira, Rafael Felipe da Costa; Filho, Ivan Roque de Barros (FapUNIFESP (SciELO), 2025)
Opossums are synanthropic animals that participate in the zoonotic transmission cycles. Chagas disease, a neglected tropical disease caused by Trypanosoma cruzi, affects many domestic and wild animals and humans worldwide. This study aimed to determine the occurrence of T. cruzi in free-ranging opossums in Canoinhas, Santa Catarina, Brazil. Fifty opossums (Didelphis albiventris) (33 captured and 17 road-killed) were evaluated using Nested-PCR assay. All tissue samples were negative (0/17). Eight of the 33 (24.24%; 95% CI:11.94–40,89%) blood samples were positive for T. cruzi. No significant associations were found between the sex (male/ female, p = 0.423), the trap area (rural/urban, p = 0.163), and positivity for T. cruzi in opossum blood samples. All samples showed 100% identity with T. cruzi (KF788250) isolated from Panstrongylus megistus in São Paulo, Brazil. The phylogenetic analysis model allocated all sequences obtained from D. albiventris to the large TcI clade of T. cruzi. This study provides the first record of T. cruzi in white-eared opossums in Canoinhas, Santa Catarina, southern Brazil.
Detecção de Trypanosoma cruzi em gambás de orelha-branca (Didelphis albiventris) em Canoinhas no Estado de Santa Catarina, Brasil
Keywords: Chagas disease; Didelphis; Trypanosoma cruzi